2008
DOI: 10.1210/en.2008-0378
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Thyroid Hormone Transporters Monocarboxylate Transporter-8 (SLC16A2) and Organic Ion Transporter-14 (SLCO1C1) at the Blood-Brain Barrier

Abstract: Thyroid hormones require transport across cell membranes to carry out their biological functions. The importance of transport for thyroid hormone signaling was highlighted by the discovery that inactivating mutations in the human monocarboxylate transporter-8 (MCT8) (SLC16A2) cause severe psychomotor retardation due to thyroid hormone deficiency in the central nervous system. It has been reported that Mct8 expression in the mouse brain is restricted to neurons, leading to the model that organic ion transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
213
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(243 citation statements)
references
References 35 publications
22
213
1
2
Order By: Relevance
“…For instance, in a recent report Roberts et al (2008) showed the expression of OATP1C1 is higher in rodents compared with human brain. However, due to the high level of homology in structure and substrate specificity between rodent and human OATP1C1, it seems plausible that OATP1C1 is also important for T 4 uptake in the human brain.…”
Section: Oatp1c1mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in a recent report Roberts et al (2008) showed the expression of OATP1C1 is higher in rodents compared with human brain. However, due to the high level of homology in structure and substrate specificity between rodent and human OATP1C1, it seems plausible that OATP1C1 is also important for T 4 uptake in the human brain.…”
Section: Oatp1c1mentioning
confidence: 99%
“…In the mouse brain, MCT8 is expressed not only in neurons but also in capillaries and the choroid plexus (Heuer et al 2005, Roberts et al 2008. The importance of MCT8 in the blood-brain barrier and in the blood-cerebral spinal fluid (CSF) barrier is strongly suggested by the almost complete block in brain T 3 uptake in MCT8 knockout mice (Trajkovic et al 2007).…”
Section: Mct8 and Mct10mentioning
confidence: 99%
See 1 more Smart Citation
“…However, brain T3 uptake is probably largely determined by transport across the blood-brain barrier (BBB) and/or the blood-CSF barrier (BCB) and indeed MCT8 is importantly expressed in brain capillaries and in the choroid plexus (7,13). The lack of effect of Mct8 inactivation on brain uptake of T4, which is also a substrate for MCT8, may be explained by assuming that T4 is largely transported across the BBB and BCF by OATP1C1 (7,13).…”
Section: Tissue and Hormone-specific Effects Of Mct8 Inactivationmentioning
confidence: 99%
“…Expression of OATP1C1 is restricted to specific areas of the adult brain, in particular in the capillary wall and in the choroid plexus, whereas MCT8 and MCT10 are widely expressed throughout the body including the brain (8,10,11,12,13,14). From the three deiodinases, types 1, 2, and 3 (D1, D2, and D3), D2 and D3 are particularly important for the regulation of intracellular TH levels in the brain (15).…”
Section: Introductionmentioning
confidence: 99%